2009
DOI: 10.1038/cr.2009.104
|View full text |Cite
|
Sign up to set email alerts
|

p28GANK inhibits endoplasmic reticulum stress-induced cell death via enhancement of the endoplasmic reticulum adaptive capacity

Abstract: It has been shown that oncoprotein p28GANK , which is consistently overexpressed in human hepatocellular carcinoma (HCC), plays a critical role in tumorigenesis of HCC. However, the underlying mechanism remains unclear. Here, we demonstrated that p28 GANK inhibits apoptosis in HCC cells induced by the endoplasmic reticulum (ER) stress. During ER stress, p28 GANK enhances the unfolded protein response, promotes ER recovery from translational repression, and thereby facilitates cell's ability to cope with the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…As ER stress activates non-UPR specific survival pathways such as PI3K/Akt and MEK/ERK in parallel with the UPR pathways, we focused on the role of c-Met in regulating non-UPR specific pathways. Because the PI3K/Akt and MEK/ ERK pathways, two downstream signaling pathways of c-Met (22), play a pivotal role in protecting cells against ER stress (28), it is reasonable to suggest that p190Met NC might inhibit thapsigargin-induced apoptosis through the PI3K/ Akt and MEK/ERK pathways. p190Met NC inhibition or knockdown led to PI3K/Akt and MEK/ERK inactivation in ER-stressed MHCC97-H and MHCC97-L cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As ER stress activates non-UPR specific survival pathways such as PI3K/Akt and MEK/ERK in parallel with the UPR pathways, we focused on the role of c-Met in regulating non-UPR specific pathways. Because the PI3K/Akt and MEK/ ERK pathways, two downstream signaling pathways of c-Met (22), play a pivotal role in protecting cells against ER stress (28), it is reasonable to suggest that p190Met NC might inhibit thapsigargin-induced apoptosis through the PI3K/ Akt and MEK/ERK pathways. p190Met NC inhibition or knockdown led to PI3K/Akt and MEK/ERK inactivation in ER-stressed MHCC97-H and MHCC97-L cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although the UPR is generally activated in various solid tumors, it is unclear how tumor cells adapt to long term ER stress. We have previously shown that HCC cells are relatively resistant to ER stress-induced apoptosis (28), but the detailed mechanisms remain largely unknown. The present work reveals that a non-canonical form of c-Met tyrosine-kinase receptor p190Met NC exerts a potent protective effect against prolonged ER stress mediated by ER Ca 2ϩ disturbance in HCC cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations